2010
DOI: 10.1590/s0103-507x2010000200014
|View full text |Cite
|
Sign up to set email alerts
|

Controle da pressão do cuff na unidade terapia intensiva: efeitos do treinamento

Abstract: Controle da pressão do cuff na unidade terapia intensiva: efeitos do treinamento INTRODUCTION Given the growing relevance of specialized physiotherapists in intensive care units (ICUs), these professionals are progressively required to have appropriate knowledge to supply these units needs. (1) The intensive care team should understand the specific pulmonary care required for each individual patient, and work as a team to establish realistic targets. (2) Invasive ventilation patients, with impaired respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 7 publications
3
6
0
11
Order By: Relevance
“…The same was seen in another study, in which the cuff pressure measurements above 30 cmH 2 O were found in the three shifts. Nevertheless, the night shift presented more cases of changes in the pressure cuff when compared with the other shifts, which presented 14% of cases (16) .…”
Section: Discussionmentioning
confidence: 88%
“…The same was seen in another study, in which the cuff pressure measurements above 30 cmH 2 O were found in the three shifts. Nevertheless, the night shift presented more cases of changes in the pressure cuff when compared with the other shifts, which presented 14% of cases (16) .…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the patient demanded a greater caloric intake required on the bedridden, the condition of the heart pump, the cardiac output and consequently irrigation and proper nutrition of organic tissues. 8,10 In this respect, it is the responsibility of the nurse to repeal the need of self-care of feeding by educational measures to clarify the patient about the necessity of having the nasogastric probe, and guide her on the care for the maintenance of the equipment.…”
Section: Resultsmentioning
confidence: 99%
“…The cuff has the function to ensure the proper pulmonary ventilation without allowing air leakage (3,(6)(7)(8) , and prevent aspiration of oropharyngeal and gastroesophageal contents into the lungs (3,(6)(7)(8)(9)(10) . The pressure in the cuff is harmful to the tracheal mucosa (6,(9)(10)(11) especially when the pressure setting is not appropriate, using extremely safe values (9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%